Resistencia de la yuca (manihot esculenta crantz) a la mosca blanca (aleurotrachelus socialis), mediante la tecnología del ADN recombinante - Cuervo, Raúl A (Universidad de San Buenaventura - Cali, 2017)
The genotype capable of yucca named MCOL 2246 was submitted to the process of transgénesis by means of the infection by the bacterium Agrobacterium tumefaciens, acquired to the American Type Culture Collection (ATCC). The bacterial strain transformed using the protocol of Chloride of Calcium of Mandel and Fig (1970), to which a “plásmido recombinante” was inserted You who was possessing two sequences of resistance to antibiotics as scoreboards, an origin of replication and the gene cry1Ab, responsibly of awarding resistance to the yuca. The bacteria recombinantes were put in touch with wounds realized to the fabric meristemático of the plants of yucca, which were expressing the gene of interest (cry 1Ab) achieving indexes of resistance to the fly in the plants of yucca transformed. The statistical design employee based on an ANOVA with a statistician of Fischer, where they find 3 treatments (T1: Control capable Yucca MCOL 2246, T2: Yucca Transgénica, T3: tolerant Yucca to the white fly MECU-72). The treatment 3 (T3) was coming from the International Center of Tropical Agriculture where one was possessing this material from crossings you will cultivate resistant. Tukey’s postanova was in use for the determination of the treatments with significant differences.